Uncovering the Causal Link Between Obesity‐Associated Genes and Multiple Sclerosis: A Systematic Literature Review - Ali Jafari; Sara Khoshdooz; Melika Arab Bafrani; Farnush Bakhshimoghaddam; Hamid Abbasi; Saeid Doaei (Brain and Behavior)
ABSTRACT Background: Multiple sclerosis (MS) is a multifaceted neurodegenerative disorder influenced by genetics and lifestyle. This systematic literature review investigates the role of six obesity‐associated genes, including fat mass and obesity‐associated (FTO), FAS apoptosis inhibitory molecule 2 (FAIM2), Niemann–Pick disease type C1‐like 1 (NPC1), glucosamine‐6‐phosphate deaminase 2 (GNPDA2), melanocortin‐4 receptor (MC4R), and brain‐derived neurotrophic factor (BDNF) in the context of MS. Methods: A literature search was executed using Embase, Scopus, Cochrane, Web of Science, and PubMed databases from inception to July 2024. The related keywords employed during the search process are “fas apoptotic inhibitory molecule 2,” “Niemann–Pick disease type C1,” “fat mass and obesity‐associated,” “melanocortin‐4 receptor,” “brain‐derived neurotrophic factor,” “glucosamine‐6‐phosphate deaminase 2,” and “multiple sclerosis.” Results: Out of 2108 papers, 27 were entered into the present systematic literature review. The FTO gene may affect MS susceptibility through metabolic and inflammatory pathways. FAIM2 and NPC1 genes may contribute to MS pathogenesis, though their precise roles are still being elucidated. The GNPDA2 gene may have some connections with MS but requires further clarification. MC4R has demonstrated significant neuroprotective and anti‐inflammatory effects, suggesting its potential impact on MS progression. BDNF plays a complex role in neuronal survival and repair and may influence the risk of MS. Conclusion: Our findings demonstrated that obesity‐related genes may have a significant impact on MS risk and disease course, revealing novel insights into the genetic underpinnings of MS.